A fuzzy AHP approach to evaluating machine tool alternatives - Ayağ, Zeki; Özdemir, Rifat Gürcan (SPRINGER, VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS, 2006)
Selecting process of a machine tool has been very important issue for companies for years, because the improper selection of a machine tool might cause of many problems affecting negatively on productivity, precision, flexibility and company's responsive manufacturing capabilities. On the other hand, selecting the best machine tool from its increasing number of existing alternatives in market are multiple-criteria decision making (MCDM) problem in the presence of many quantitative and qualitative attributes. Therefore, in this paper, an analytic hierarchy process (AHP) is used for machine tool selection problem due to the fact that it has been widely used in evaluating various kinds of MCDM problems in both academic researches and practices. However, due to the vagueness and uncertainty on judgments of the decision-maker(s), the crisp pair wise comparison in the conventional AHP seems to insufficient and imprecise to capture the right judgments of decision-maker(s). That is why; fuzzy number logic is introduced in the pair wise comparison of AHP to make up for this deficiency in the conventional AHP. Shortly, in this study, an intelligent approach is proposed, where both techniques; fuzzy logic and AHP are come together, referred to as fuzzy AHP. First, the fuzzy AHP technique is used to weight the alternatives under multiple attributes; second Benefit/Cost (B/C) ratio analysis is carried out by using both the fuzzy AHP score and procurement cost, of each alternative. The alternative with highest B/C ratio is found out and called as the ultimate machine tool among others. In addition, a case study is also presented to make this approach more understandable for a decision-maker(s).
Keywords: machine tool selection; fuzzy logic; multiple-criteria decision making; analytic hierarchy process (AHP); Benefit/Cost (B/C) ratio analysis; decision-support system; manufacturing systems; product development; selection; model; environment; design; tezgah seçimi; Bulanık mantık; Çok kriterli karar verme; analitik hiyerarşi süreci (AHP); Fayda / Maliyet (F / M) oranı analizi; karar destek sistemi; imalat sistemleri; ürün geliştirme; seçim; model; çevre; dizayn